Effect of Monopolar Versus Bipolar Transurethral Resection of The Prostate on Erectile Function: A Randomized Controlled Trial with Phosphodiesterase-5 Inhibitors Users Subgroup Analysis - Khorrami , Farbod; Sadat , Seyyed-Masoud; Hajian , Mohammadreza; Gholipour, Farshad (Urology Journal, 2025)
Purpose: Men with lower urinary tract symptoms (LUTS) from benign prostatic hyperplasia (BPH) often experience erectile dysfunction (ED). While transurethral resection of the prostate (TURP) can improve ED, new onset ED remains a concern. This study compares monopolar (M TURP) and bipolar (B TURP) techniques, with a subgroup analysis based on phosphodiesterase 5 inhibitor (PDE5i) use. Materials and Methods: This randomized clinical trial included candidates for TURP aged over 50 years. Patients were divided into M TURP and B TURP groups. Erectile function was assessed using the International Index of Erectile Function 15 (IIEF 15) at baseline, six weeks, and six months post surgery. Results: A total of 205 patients were analyzed (102 M TURP, 103 B TURP). Baseline characteristics, perioperative findings, and surgical complications were similar. IIEF 15 scores were comparable between groups at all time points. In the PDE5i user subgroup, M TURP showed a slight short term decline in erectile function and total scores at 6 weeks, but both groups demonstrated no significant long term changes at 6 months. Conclusion: No significant difference was observed between M TURP and B TURP on erectile function during medium term follow up. Patients with prior PDE5i use may experience fewer short term adverse effects on erectile function from B TURP.